2013
DOI: 10.1111/mec.12535
|View full text |Cite
|
Sign up to set email alerts
|

Integrating multiple lines of evidence to better understand the evolutionary divergence of humpback dolphins along their entire distribution range: a new dolphin species in Australian waters?

Abstract: The conservation of humpback dolphins, distributed in coastal waters of the Indo-West Pacific and eastern Atlantic Oceans, has been hindered by a lack of understanding about the number of species in the genus (Sousa) and their population structure. To address this issue, we present a combined analysis of genetic and morphologic data collected from beach-cast, remote-biopsied and museum specimens from throughout the known Sousa range. We extracted genetic sequence data from 235 samples from extant populations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 72 publications
3
84
0
1
Order By: Relevance
“…The Indo-Pacific humpback dolphin Sousa chinensis inhabits coastal waters of the Indian and western Pacific Oceans (Jefferson & Karczmarski 2001, Reeves et al 2008 and is found predominantly close inshore in waters less than 20 m deep (Karczmarski 1999, 2000, Jefferson & Karcz marski 2001, Reeves et al 2008, Ross et al 2010, Mendez et al 2013). This restricted inshore distri bution exposes humpback dolphins to various anthropogenic impacts, such as incidental mortality in fishing gear (bycatch), vessel collisions, resource de pletion, bioaccumulation of harmful pollutants and habitat destruction through direct human activities (Jefferson & Karczmarski 2001, Reeves et al 2008, Jefferson et al 2009, Ross et al 2010, Huang et al 2013, Slooten et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The Indo-Pacific humpback dolphin Sousa chinensis inhabits coastal waters of the Indian and western Pacific Oceans (Jefferson & Karczmarski 2001, Reeves et al 2008 and is found predominantly close inshore in waters less than 20 m deep (Karczmarski 1999, 2000, Jefferson & Karcz marski 2001, Reeves et al 2008, Ross et al 2010, Mendez et al 2013). This restricted inshore distri bution exposes humpback dolphins to various anthropogenic impacts, such as incidental mortality in fishing gear (bycatch), vessel collisions, resource de pletion, bioaccumulation of harmful pollutants and habitat destruction through direct human activities (Jefferson & Karczmarski 2001, Reeves et al 2008, Jefferson et al 2009, Ross et al 2010, Huang et al 2013, Slooten et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…However, dramatic declines along the urban coast of Queensland are evident from catch per unit effort data in shark nets for bather protection along the Queensland coast from 1962 to 1999, and dugongs are impacted by multiple threats including incidental bycatch in fishing nets, loss of seagrass, vessel strike, illegal poaching, and legal indigenous hunting in northern Australian waters (104). Two inshore dolphins, the Australian snubfin dolphin, Orcaella heinsohni, and Australian humpback dolphin, Sousa sahulensis, also face a similar range of threats from fisheries bycatch, habitat degradation, vessel strike, pollution, and acoustic disturbances (6,7). For Australia's marine mammals, our review concluded that six species are threatened, with a further five species Near Threatened, but a much higher proportion (60%) are Data Deficient.…”
Section: Significancementioning
confidence: 99%
“…Australia's terrestrial mammal fauna is the most distinctive in the world (5), including ancient lineages of monotremes, very diverse marsupials, and a wide range of eutherians: 87% of Australia's 316 terrestrial mammal species are endemic. The Australian marine mammal fauna is also diverse (58 species) but has a lower rate of endemism: one pinniped species and two near-endemic cetacean species (6)(7)(8).…”
mentioning
confidence: 99%
“…There are now increasing prospects and proposals for development in coastal waters of northern Australia, and, consequently, there are concerns about the conservation of the following three species of coastal dolphins occurring in these waters Allen et al 2012;Bejder et al 2012;Cagnazzi et al 2013;Palmer et al 2014): the Australian snubfin, Orcaella heinsohni (hereafter snubfin), a new as-yet-unnamed species of humpback dolphin, Sousa sp. (Frère et al 2011;Mendez et al 2013), and the bottlenose dolphins, Tursiops sp.…”
Section: Introductionmentioning
confidence: 99%